Latent profile analysis of nurses’ moral resilience and its influencing factors - Zheng, Zhihui (Nursing ethics, 2026)
Background Nurses often face complex moral distress in clinical practice, where maintaining emotional stability and making moral decisions under pressure is crucial for patient care and safety. Moral resilience helps nurses stay composed, think rationally, and navigate moral challenges effectively. Exploring the characteristics and influencing factors of different moral resilience subgroups can provide insights into nurses? resilience levels and inform targeted interventions to enhance their occupational well-being.Aim To identify the latent profile model of moral resilience in nurses and analyze the characteristic differences and influencing factors across different profiles.Design A multicenter cross-sectional study.Participants and research context The study involved nurse practitioners from nine different hospitals. A total of 1098 nurses from different specialties participated in the study.Ethical considerations The study was approved by the ethical board of the 900 Hospital of the Joint Service Support Force.Findings Nurses? moral resilience was classified into three profiles: Vulnerable (46.45%), Discrepant (12.02%), and Robust (41.53%). Divorced or widowed nurses (p = .017, Z = 2.395) and those working in infectious disease departments (p < .001, Z = 3.796) were more likely to belong to the Robust profile. Higher moral distress increased the likelihood of being in the Vulnerable profile (p = .017/<.001, Z = ?2.379/?7.001). A stronger ethical climate (p < .001, Z = 4.540) and greater workplace trust (p = .010, Z = 2.586) were more likely to belong to the Robust profile. Nurses with greater moral courage were more likely to have robust moral resilience and less likely to be in the Discrepant profile (p = .007/<.001, Z = 2.687/?5.225).Conclusion Nurses? moral resilience is heterogeneous, highlighting the need for managers to consider profile characteristics and specialty-specific factors. Strengthening the hospital ethical climate can reduce moral distress, enhance workplace trust, and foster moral courage, ultimately improving moral resilience in nurses.